The development, implementation, and evaluation of the Logan Strides, an eighth-grade after-school program at Logan Middle School, La Crosse, WI - Anderson, Kjirsten L. (My University, 2017)
This graduate project details the development, implementation, and evaluation of a sixweek Logan Strides program, for the Logan Middle School in La Crosse, WI. The program was borne out of adolescent and community need. The creation of the five different weekly lesson plans was guided by the Purdue Extension-Healthy Body Image: A Lesson Plan for Middle School Students, the project author's research on related literature, along with her professional and personal experience, and a Logan Middle Teacher. The program experience, targeted vulnerabilities for that age group, along with promoting physical activity and healthful nutrition choices. At the end of the Logan Strides program was the opportunity for the students to participate in a local 5K. The program was assessed weekly with process evaluations, as well as a matched pre- and post-assessment, and lastly with a post-program questionnaire. The findings from the evaluations revealed participants' positive behavior change, healthful habits, and improved body image. Recommendations were drawn from the program findings and conclusions. The project author intended to have the health promotion program continue at Logan Middle School in the following school years, with volunteer help, and to provide an available guide for the development of similar programs in the future.
Keywords: Exercise therapy; Exercise tests; Kinesiology